A new Myxobolus (Cnidaria: Myxosporea) infecting the ornamental catfish Corydoras schwartzi from the Purus River in Brazil - Mathews, Patrick D.; Madrid, Rafael R.M.; Mertins, Omar; Rigoni, Vera L.S.; Morandini, André C. (European Journal of Taxonomy, 2020)
A new microscopic cnidarian is described, infecting five of thirty (16.6%) specimens of Corydoras schwartzi caught in the Purus River, State of Amazonas, Brazil. Histological analysis showed that cyst development occurred in the serosa layer of the intestine. Mature myxospores are ovoid in body shape in frontal view, 22.4 ± 0.3 μm in total length and 16.3 ± 0.1 μm in width. Internally, two aubergine-shaped, elongate symmetrical polar capsules occupy more than half the length of the spore, 14.3 ± 0.2 μm in length and 6.5 ± 0.1 μm in width. Ultrastructural analysis provided evidence of five polar filament coils inside the polar capsule and binucleated sporoplasm containing a moderate number of sporoplasmosomes. The valvogenic cells abutting each other form a sutural ridge and frequently a thin layer of homogeneous material separates the cells. The outer surface of the myxospore valves is smooth, with no evidence of formation of ridges in the valves. Immature myxospores in various stages of development were observed. This study is the first report of a myxosporean parasitizing C. schwartzi and the first report of a myxosporean infection in the intestine of an ornamental fish from South America.